PELATIHAN PEMBUATAN SAOS SAMBAL DI KAMPUNG YABA MARU DISTRIK TANAH MIRING KABUPATEN MERAUKE - Wahida Wahida; Elly Noer; Sajriawati Sajriawati (Musamus University, 2020)
Through food processing technology, chili and tomatoes can be processed into more practical products. One of the popular chili preparations is chili sauce. Processed sauce use as a seasonings, add flavour to the food, and complement the dish. The purpose of this community service activity is to provide additional knowledge to the people of Yaba Maru Village on how to make a hygienic and durable chili sauce, that give economic advantage to the people. Yaba Maru village is one of the villages in the Tanah Miring District of Merauke Regency, which has abundant chili and tomato production. For the Yaba Maru community, tomatoes and chili are usually directly sold in raw form without processing. If the production are abundant, chili and tomatoes will be sold cheaply. Based on this, it is necessary to do community service activities that provide training on making chili sauce, to increase community knowledge and eventually increase the income of the community, especially for women or housewives. The method used in this service activity consists of training in making chili sauce, completed with how to package the sauce, to increase the quality and selling value of the products.